Tuberculosis in children and adults: two distinct genetic diseases - Alcaïs, Alexandre (The Rockefeller University Press, 2005)
Disseminated disease in children and pulmonary disease in adults constitute two major epidemiological and clinical forms of tuberculosis. Paradoxically, only a small fraction of infected individuals develop clinical tuberculosis, typically one form of the disease or the other. Mendelian and complex genetic predispositions to tuberculosis were reported recently in children and adults, respectively. Here, we argue that tuberculosis and its clinical expression largely reflect the underlying human genetic background.